RELIABILITY ALLOCATION OF CNC LATHE BASED ON EDGEWORTH SERIES METHOD AND DATE ENVELOPMENT ANALYSIS - ZHANG YiMin; JIA JingCun; HUANG XianZhen (Jixie qiangdu)
The reliability of CNC lathe was allocated based on the failure information of CNC lathe. It used Edgeworth series method to expand the fault data into standard normal variable expansion to obtained the reliability. Tested with data fitting method,the distribution curve of Edgeworth was well resembled. To obtain subsystem reliabilities,the Edgeworth series method was introduced. Concentrating three kinds of influence factors from the perspective of fault information,the allocation model based on Date Envelopment Analysis（ DEA） was proposed. Based on failure information of CNC lathe,this method was considerably practical to improve the redistribution of the machine’s reliability.